A revision and phylogenetic analysis of the spider genus Oxysoma Nicolet (Araneae: Anyphaenidae, Amaurobioidinae) - Aisen, Santiago; Ramírez, Martín J. (Zootaxa, 2015)
We review the spider genus Oxysoma Nicolet, with most of its species endemic from the southern temperate forests in Chile and Argentina, and present a phylogenetic analysis including seven species, of which three are newly described in this study (O. macrocuspis new species, O. kuni new species, and O. losruiles new species, all from Chile), together with other 107 representatives of Anyphaenidae. New geographical records and distribution maps are provided for all species, with illustrations and reviewed diagnoses for the genus and the four previously known species (O. punctatum Nicolet, O. saccatum (Tullgren), O. longiventre (Nicolet) and O. itambezinho Ramírez). The phylogenetic analysis using cladistic methods is based on 264 previously defined characters plus one character that arises from this study. The three new species are closely related with Oxysoma longiventre, and this four species compose what we define as the Oxysoma longiventre species group. The phylogenetic analysis did not retrieve the monophyly of Oxysoma, which should be reevaluated in the future, together with the genus Tasata.